Analysis of coastal management strategies in responding to shoreline changes in Karimunjawa and Kemujan Islands of Central Java, Indonesia - Suryanti, Suryanti; Muskananfola, Max Rudolf; Febrianto, Sigit; A'in, Churun (Journal of Degraded and Mining Lands Management, 2025)
The Karimunjawa National Park area has various coastal resources and ecosystems, such as mangrove forests, seagrass, and coral reefs, which provide a habitat for several vital organisms. The presence of natural and human factors in coastal areas causes environmental degradation. Changes in environmental conditions, increasing population, and land requirements in Karimunjawa National Park can have negative impacts if not appropriately managed. Therefore, coastal management strategies are needed to maintain sustainability and prevent the extinction of coastal resources. The research locations are Karimunjawa Island and Kemujan Island. This research aimed to develop a coastal management strategy based on changes in the shoreline of Karimunjawa Island and Kemujan Island. The SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis model was used to identify coastal management strategies through the most effective priority scale. The research results showed that in 2008-2023, the average erosion on Karimunjawa Island was -11.41 m or -0.75 m/year, and accretion was 13.30 m or 0.87 m/year, while the average erosion on the island rainfall was -13.74 m or -0.90 m/year and accretion is 13.30 m or 1.07 m/year. Management strategies that can be implemented are (1) forming a board or committee; (2) conducting outreach and education activities; (3) identifying critical areas; (4) developing protection and utilization programs; (5) conducting research; (6) monitoring; (7) formulating policies.